Diastereocontrol in the Synthesis of 2,3,4-Trisubstituted Pyrrolidines and Tetrahydrofurans via a Palladium(II)-Catalyzed Three-Component Coupling Reaction - Raikar, Sandeep; Pal, Benoy Kumar; Malinakova, Helena C. (Synthesis, 2012)
The synthesis of trisubstituted pyrrolidines and tetrahydrofurans from boronic acids, allenes, and imines or aldehydes via a five- and a three-step protocol, respectively, is described. The assignment of the relative stereochemistry in the pyrrolidines and tetrahydrofurans confirmed the mechanistically significant stereochemical divergence of the palladium-catalyzed three-component coupling reaction. The methodology is applicable to the preparation of combinatorial libraries of pyrrolidines related to pharmaceutical agents and bioactive natural products.
Keywords: stereoselective synthesis; heterocycles; palladium; multicomponent reactions; ring closure